"further proof of the robust nature of the local economy": macroeconomics as architectural driver of Palmerston North's Civic Administration Building - Schmidt, Tyson (Architectural History Aotearoa, 2022)
The Civic Administration Building in Palmerston North is often rated the ugliest building in the city. Dreamed of at the start of the 1970s, it was seen as eventually being the physical manifestation of Palmerston North's big city status (once Hamilton had been defeated). By the time it was completed at end of the decade it was a monument to austerity, having survived rampant inflation and central Government controls, and proudly declared as a "solid, practical unobtrusive building." This paper explores how the macroeconomic conditions of the 1970s shaped this transition from dream to practical necessity.